FOMO and Flash Sales Driving Impulsive Skincare Purchases: The Mediating Role of Spontaneity in Gen Z - Karina Gusriani; Ridwan Sofyandi; Yuliati Yuliati; Siti Salamah Hartati Ningsih; Popy Novita Pasaribu (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2026)
Study examines the influence of Fear of Missing Out (FOMO) and flash sales on impulsive purchases of skincare products by Generation Z in Indonesia, with an emphasis on the mediating role of spontaneity in the decision-making process. Using the Stimulus-Organism-Response (SOR) theoretical framework and the PLS-SEM approach, this study involved 339 respondents from Bogor City who actively shop through social commerce. The results show that FOMO and flash sales significantly influence spontaneity, which then acts as a mediator in driving impulsive buying behaviour. These findings confirm that psychological factors are more influential than direct promotional stimuli and emphasize the importance of digital marketing strategies that can evoke emotions and a sense of urgency. The practical implication is that MSMEs can leverage this phenomenon through content that creates a sense of exclusivity and urgency, to increase sales effectively and sustainably in the digital era.